2018
DOI: 10.1002/lary.27634
|View full text |Cite
|
Sign up to set email alerts
|

Risk and outcomes for second primary human papillomavirus–related and –unrelated head and neck malignancy

Abstract: Objectives/Hypothesis To 1) examine the characteristics of patients who develop second primary malignancies (SPMs) from an index human papillomavirus (HPV)‐related head and neck squamous cell carcinoma (HNSCC) and HPV‐unrelated HNSCC and to 2) compare overall survival between those with HPV‐related and HPV‐unrelated index HNSCC among patients who develop SPM. Study Design Retrospective cohort analysis. Methods A retrospective study was conducted of 113,259 patients who were diagnosed with HNSCC from 2000 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…Thus, Morris et al reviewed 75 087 patients with HNC and found that before the 1990s, hypopharynx and oropharynx cancers carried the highest risk of SPT, since then, during the HPV era, SPT risk associated with oropharyngeal cancer has declined to the lowest risk level of any subsite. A recent retrospective study in a large cohort of HNC patients also showed that patients with HPV‐related tumors has a lower risk of development of SPTs …”
Section: Introductionmentioning
confidence: 96%
“…Thus, Morris et al reviewed 75 087 patients with HNC and found that before the 1990s, hypopharynx and oropharynx cancers carried the highest risk of SPT, since then, during the HPV era, SPT risk associated with oropharyngeal cancer has declined to the lowest risk level of any subsite. A recent retrospective study in a large cohort of HNC patients also showed that patients with HPV‐related tumors has a lower risk of development of SPTs …”
Section: Introductionmentioning
confidence: 96%
“…Oncogenic HPV subtypes are thought to be responsible for more than 90% of anal, 70% of oropharynx, and 60% of penile cancers (National Vaccine Advisory Committee, 2016, World Health Organization, 2016). HPV infection is not only associated with primary cancers but are also attributable to second primary cancers (Adjei Boakye et al, 2018b, Adjei Boakye et al, 2018c, Adjei Boakye et al, 2018a, Adjei Boakye et al, 2019). More than 40% of all HPV-related cancers in the US occur in men (Viens et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From a total of 829 articles obtained after deleting duplicates, 703 were excluded based on title and abstract and 126 after reading the full text (Figure 1 ). Finally, 38 articles were included in this systematic review: 36 cohort studies (Adams et al, 2019 ; Adjei Boakye et al, 2019 ; Arie et al, 2021 ; Bertolini et al, 2021 ; Bosshart et al, 2021 ; Bugter et al, 2021 ; Bukovszky et al, 2022 ; Cadoni et al, 2017 ; Chow et al, 2019 ; Feng et al, 2017 ; Guo et al, 2021 ; Harada et al, 2017 ; Ho et al, 2022 ; Hosokawa et al, 2018 ; Inoue et al, 2021 ; Iwatsubo et al, 2019 ; León et al, 2020 ; Leoncini et al, 2018 ; Li et al, 2020 ; Lin et al, 2020 ; Liu et al, 2017 ; Martel et al, 2017 ; Milliet et al, 2021 ; Min et al, 2019 ; Nishimura et al, 2021 ; Overwater et al, 2022 ; Petersen et al, 2022 ; Piersiala et al, 2020 ; Sawaf et al, 2022 ; Stepan et al, 2022 ; Su et al, 2019 ; Su et al, 2020 ; Tseng et al, 2017 ; Wang et al, 2017 ; Wang et al, 2019 ; Zhang et al, 2019 ) and 2 case‐control studies (Ni et al, 2018 ; Watanabe et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent SPT sites analysed were oesophagus ( n = 22) and lung ( n = 19). Four studies did not report the SPT location (Adjei Boakye et al, 2019 ; Cadoni et al, 2017 ; Liu et al, 2017 ; Tseng et al, 2017 ). Age and sex were variables evaluated in all studies, except in Harada et al ( 2017 ), Sawaf et al ( 2022 ), Stepan et al ( 2022 ) and Bukovsky et al ( 2022 ) (the last one evaluated sex but not age).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation